The assessment of the visual perception in viewshed analysis for the landscape settings - Enrico Fabrizio; Gabriele Garnero (Journal of Agricultural Engineering, 2013)
Visibility studies for rural and forest landscape are well established and conducted by means of standard GIS tools that compute the viewshed (a binary representation of the visibility of a location from a certain viewpoint) and cumulative viewsheds (integer representations of the visibility of a location from more viewpoints obtained with raster algebra). However, in order to go beyond the sole geometric information if a cell is visible or not, some authors have introduced various concepts that are based on the visual magnitude or visual exposure. These concepts also take into account the target magnitude, the atmospheric extinction, the colour difference to the background and the visual acuity. These calculations may be complex, extremely time consuming and not affordable with standard GIS tools, because they require specific programming tools. Besides, depending on the application, the factor that affects the visibility may be the distance, the atmospheric extinction, the contrast, etc. In this work, we concentrate on the problem of the calculation of the landscape sensitivity, which defines the degree to which a given landscape is potentially affected by possible changes by means of viewsheds analyses. An example in rural settings is presented in order to demonstrate the problems that arise in real applications and the possible solutions.